Aux origines de la privatisation du financement du soin : quand la théorie de l’aléa moral rencontre le capitalisme sanitaire - Philippe Batifoulier (Revue de la Régulation)
Health care financing in Europe has become more private because of the retrenchment of public health insurance, the increased reliance on private insurance, greater cost-sharing and household out-of-pocket payments. This article presents an analysis of the legitimacy of this process of privatization in health care which comes from a representation of the medical coverage reduced to a problem of financial incentive. The framework for this privatization draws on a convention under the influence of the convergence of the mainstream economic theory and health capitalism. The “lessons” of the moral hazard theory in health economics is that cost sharing and private health insurance can reduce health spending without damage on health status. This “lesson” has been enormously influential on policy makers and justifies the marketization of health care. This paper shows that this theoretical and political background is scientifically deficient and leads to perverse effects: inducement of inequalities, increase in health spending and social secession.